Penegakan Hukum terhadap Penyalahgunaan Senjata Tajam oleh Geng Motor di Kota Jambi - Zamzimi, Padlan (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the law enforcement against the misuse of sharp weapons by Motorcycle Gangs in Jambi City and the obstacles faced by the Police in carrying out the enforcement and the efforts made by the Police in overcoming these obstacles. The approach method used in this study is empirical juridical. The results of the study are that law enforcers have implemented the right procedures in handling cases of misuse of sharp weapons, starting with raids on the highway followed by the detention of perpetrators who are proven to be carrying sharp weapons illegally. However, the Jambi Police face a number of obstacles in implementing law enforcement against this crime. These obstacles include the legal aspect itself, limited human resources for law enforcement, lack of facilities and infrastructure, and low public awareness. To overcome these obstacles, the police have taken several strategic steps. First, establishing cooperation with the Intelligence Directorate to prevent the misuse of sharp weapons and strengthening coordination with the Regional Police Chiefs throughout Indonesia. Second, increasing the motivation and competence of personnel through special training that focuses on crimes related to sharp weapons. Third, encouraging changes in legal policies that are relevant to this crime.